2017
DOI: 10.1016/j.ijid.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Short-course antimicrobial treatment for acute cholangitis with Gram-negative bacillary bacteremia

Abstract: The results of this study suggest that acute cholangitis with Gram-negative bacillary bacteremia can be treated safely with a shorter antimicrobial treatment duration of <14 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 10 publications
(10 reference statements)
0
48
0
Order By: Relevance
“…The authors assessed clinical cure and bacteriological eradication among the compared treatment groups and found that there was no significant difference in either cure or eradication rates between shortand long-course treatment (78.6% versus 86.8%, respectively; P ϭ NS; and 83.3% versus 89.7%, respectively; P ϭ NS). Finally, 1 study referred to patients treated for bacteremia (25). No significant difference was found in mortality between short-and long-course treatment in that study (0% versus 5.7% for Ͻ14 days and Ն14 days, respectively; P ϭ NS), but relapse was higher among patients who were treated for Ն14 days than those treated for Ͻ14 days (13.3% versus 0%, respectively; P Ͻ 0.05).…”
Section: Figmentioning
confidence: 88%
See 3 more Smart Citations
“…The authors assessed clinical cure and bacteriological eradication among the compared treatment groups and found that there was no significant difference in either cure or eradication rates between shortand long-course treatment (78.6% versus 86.8%, respectively; P ϭ NS; and 83.3% versus 89.7%, respectively; P ϭ NS). Finally, 1 study referred to patients treated for bacteremia (25). No significant difference was found in mortality between short-and long-course treatment in that study (0% versus 5.7% for Ͻ14 days and Ն14 days, respectively; P ϭ NS), but relapse was higher among patients who were treated for Ն14 days than those treated for Ͻ14 days (13.3% versus 0%, respectively; P Ͻ 0.05).…”
Section: Figmentioning
confidence: 88%
“…Table 2 presents four studies which used a cutoff other than the 10 days for the classification of treatment as "short" or "long" course. Two of them were double-blind randomized controlled trials (23, 24), 1 was a retrospective cohort study (25), and 1 was a retrospective case-control trial (22). Of those studies, 3 included patients with bacteremia secondary to a single source of infection.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Uno et al compared retrospectively the outcomes among patients with bacteremic acute cholangitis due to Gram‐negative bacilli who received antimicrobial therapy over either 14 or 10 days. There were no differences between the two groups in 30‐day mortality and recurrence rate within 3 months.…”
Section: How Should Highly Resistant Causative Organisms Be Managed Imentioning
confidence: 99%